DISPARITY OF BULLYING CRIMINAL SANCTIONS REGARDING VICTIM PROTECTION - Mulyana, Yusep (Journal of Innovation Research and Knowledge, 2024)
The disparity in the judge's considerations that occurred regarding the two decisions regarding the criminal act of bullying was due to the fact that the judge had the authority to impose a sentence based on the chronological background and aim and cause of the criminal act. As well as other reasons, such as the law which in essence only provides provisions for minimum and maximum limits of sanctions, which means that the nature of the sanctions is uncertain, apart from that, the methods used for criminal acts are different, even though the case is the same, the impacts caused are also different and not the same. , as well as the consideration of the panel of judges in several situations during the course of the trial, also considering and paying attention to the condition of the defendant. As in the Child Protection Law, it provides special protection guarantees for children who are in conflict with the law, whether children as victims or children as perpetrators, especially in cases of bullying. Victimology recognizes the rights of victims. This point of view is very important because bullying is seen as something that happens in childhood and is not seen as a problem. Despite the fact that bullying has very real effects, the rights of victims have not been widely recognized from this perspective. Because witness and victim protection institutions only exist at the center and do not yet exist in the regions, Law Number 31 of 2014 concerning Witness and Victim Protection cannot be implemented effectively to handle victims and accompany them during the legal process. so that only relevant organizations and the police can protect witnesses and victims.